Effects of Collaborative Learning Strategy on Social Studies Teaching Of Citizenship Components on Upper Basic Students’ Attitude and Achievement in Akwanga, Nassarawa State, Nigeria - Balewa, Jatau Istifanus; J. Umaru, Ruth; A. Ariya, Dauda; Ridwan, Muhammad (BIRCU, 2025)
This study investigated the effects of collaborative learning strategy on upper basic students’ attitude and achievement in the citizenship components of Social Studies in Akwanga Local Government Area, Nassarawa State, Nigeria. Answering three research questions and testing two hypotheses. The study employed a quasi-experimental design, 55 Upper Basic Two students from two public schools were sampled, with one group exposed to collaborative learning and the other to conventional lecture methods. The Social Studies Achievement Test (SSAT) and Social Studies Attitude Questionnaire (SSAQ) were used for data collection after validation and reliability testing. Descriptive and inferential statistics were used in analysis of the data. Results revealed that students taught through collaborative learning demonstrated significantly higher improvements in both attitude and achievement compared to those taught by traditional methods. Additionally, no significant difference in achievement was found between male and female students in the collaborative learning group, indicating the strategy’s inclusiveness. The findings align with literature emphasizing the benefits of interactive, student-centered teaching approaches for fostering civic knowledge, skills, and positive dispositions essential for democratic citizenship. The study highlights social learning theory as a theoretical foundation, underscoring the importance of peer interaction and observation in shaping learning outcomes. Given the observed variability and concerns over students’ civic attitudes and academic performance, the study advocates the integration of collaborative learning strategies into Social Studies instruction to enhance engagement and learning effectiveness. This approach promises to produce more responsible, informed citizens equipped to contribute meaningfully to national development. The study recommends that educators and policymakers prioritize collaborative learning methods, develop inclusive environments supporting all learners, and provide professional development aligning pedagogy with evolving educational goals in citizenship education.